Identidades midiáticas: a construção da identidade de ciência na revista Galileu - Flores, Natália Martins (2012)
This research has as its theme the construction of identity of science in the media. It is justified in the context of mediatization, where the media acquires a central role in constructing representations of reality and of identities which influence the way the subjects represent the social world (SODRÉ, 2002). The central objective is to analyze the construction of identity of science in Galileu magazine by the theoretical and methodological basis of Discourse Analysis. We evaluated the extent to which the publication adopts a monophonic or polyphonic tone according to Bakhtin. The corpus covers six cover reports of Galileu with the subject of health and cognition, selected from April 2010 to July 2011. The analysis is divided into: analysis of the context of discourse production and discourse analysis. The context analysis used an interview with the current managing editor of the magazine as a tool for data collection. The discourse analysis is divided into four steps: 1) identification of speakers and enunciators of the corpus, 2) description of the ideological formations (IFs) of which these views (enunciators) originate themselves and 3) materialization of these IFs in discourse by the localization of discursive formations (DFs) that compose Galileu and 4) analysis of the relation that DFs build between each other in the discourse. The results show the discursivity of Galileu constructed by a confluence of voices and identities of science related to the IFs of modernity and postmodernity. Its discursivity comes as polyphonic in most of the corpus, due to equipollence, plenivalence and immiscible among these voices. Voices from scientific community are shown as plenivalents, while voices from common sense illustrate and support scientific discourse.